Platelet Activation by Antiphospholipid Antibodies Depends on Epitope Specificity and is Prevented by mTOR Inhibitors - Hollerbach, Anne; Müller-Calleja, Nadine; Ritter, Svenja; Häuser, Friederike; Canisius, Antje; Orning, Carolin; Jurk, Kerstin; Lackner, Karl J. (Thrombosis and Haemostasis, 2019)
Antiphospholipid antibodies (aPL) have been reported to activate platelets. This is considered to be one of the pathogenic properties of aPL. Even though aPL heterogeneity is quite well established, little is known, if the ability to activate platelets is common to all aPL or depends on antigen specificity. To further study this issue, we analyzed the ability of three human monoclonal aPL with distinctly different antigenic specificities to activate platelets in vitro. The results obtained with human monoclonal aPL were validated with immunoglobulin G (IgG) fractions obtained from patients with antiphospholipid syndrome (APS). A co-factor-independent human monoclonal anticardiolipin aPL had no discernible effect on human platelets. Two monoclonal aPL reactive against β2 glycoprotein I (β2GPI) induced platelet aggregation, integrin αIIbβ3 activation and P-selectin surface expression. These data could be confirmed with patient IgG fractions which could only induce aggregation, if they had anti-β2GPI activity. Anti-β2GPI aPL-induced platelet activation depended on interaction of aPL with the low affinity Fcγ-receptor IIa on the platelet surface. It was completely abolished by pretreatment of platelet-rich plasma with the mechanistic target of rapamycin (mTOR) inhibitors rapamycin or everolimus. This extends previous data showing that mTOR is involved in signaling of anti-β2GPI in monocytes and endothelial cells. In conclusion, anti-β2GPI aPL activate platelets while co-factor-independent anticardiolipin aPL have no effect. mTOR is involved in this signaling process which has implications beyond APS, because so far the role of mTOR signaling in platelets is incompletely explored and requires further study.
Keywords: antiphospholipid syndrome; anticardiolipin antibodies; anti-β2-glycoprotein I antibodies; platelets; rapamycin